2019
DOI: 10.15446/agron.colomb.v37n1.71681
|View full text |Cite
|
Sign up to set email alerts
|

The importance of non-monetary cost in start-up and annual cacao (Theobroma cacao L) production activities in Santander, Colombia

Abstract: Based on a double-phase methodology (grouping by cluster method and costing) the costs of three activities of cacao establishment and annual management in San Vicente de Chucuri and El Carmen de Chucuri (Santander, Colombia) were structured. The grouping phase identified two productive typologies, one with low technification level and another with a medium level; moreover, technification levels were corroborated through cost structuring, in which, for all the activities, the medium technification typology gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…General cocoa budges showed that the most important item is labor, followed by inputs and plant material. The disaggregation of costs into monetary and non-monetary (implicit cost) showed that producers with low technification and low frequency of input use present 35% of non-monetary costs per tree, while producers with some level of crop management and relatively high execution of activities have a slightly higher non-monetary cost, 45% of the average total cost per tree (Zabala et al, 2019).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…General cocoa budges showed that the most important item is labor, followed by inputs and plant material. The disaggregation of costs into monetary and non-monetary (implicit cost) showed that producers with low technification and low frequency of input use present 35% of non-monetary costs per tree, while producers with some level of crop management and relatively high execution of activities have a slightly higher non-monetary cost, 45% of the average total cost per tree (Zabala et al, 2019).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%